THE HYPERBOLIC RADON TRANSFORM AND SOME OF ITS APPLICATION IN SEISMIC DATA PROCESSING - Suprajitno Munadi (Testing Center for Oil and Gas LEMIGAS, 1992)
The Radon transform has been used in exploration seismology for a decade. It consists of stacking seismic traces along a line of constant ray parameter p. this transform is used to map seismic data from time distance space into tau-p space, where tau is the intercept time.